UPAYA MENINGKATKAN KETERAMPILAN MENULIS PROPOSAL MAHASISWA PROGRAM STUDI DIII KEPERAWATAN SOLOK POLTEKKES KEMENKES PADANG - Elan Halid; Zona Rida Rahayu; Redo Andi Marta; Mega Putri; Rini Wirasty. B (ASOSIASI IDEBAHASA KEPRI, 2023)
Writing is a productive and expressive activity. For this writing activity, the writer must be proficient in grammar, language structure, and vocabulary. Like writing a research proposal, this writing skill will not come naturally but must be developed through extensive practice. The proposal plays a crucial role in research activity. Like people who want to take a trip, a proposal is a map that describes the journey's location, direction, and a path that must be passed to get to the destination. Partners have reported several issues related to the point of writing research proposals, including the inability of students to develop an appropriate problem or research topic, a suitable framework for writing a proper proposal by the rules of scientific writing, fair use of language, and accuracy when composing proposals. The Solok DIII Nursing Study Program, 2015 cohort students, are trained through lecture methods, discussions, and proposal writing exercises in order to carry out community service activities. Lectures are conducted by providing explanations and information on how to write a good and correct proposal based on the Improved Indonesian Spelling (EYD) rules. Five lecturers serve as source persons for the Student Creativity Program (PkM) and help students understand the subject matter. Participants can generally accept the information that has been presented by the source person well as a different approach to help students learn how to formulate good and correct research problems/topics, develop a good and proper framework for writing proposals by the rules of scientific writing, use appropriate language, also excellent and accurate proposal writing. The extent to which student knowledge improves can be used as a performance indicator of the success of extension activities, discussions, and training. Although they need a lot of writing practice, students can understand the framework for creating proposals due to the presentation of information from source persons.